The Use of Arbuscular Mycorrhizal Fungi to Improve Strawberry Production in Coir Substrate - Robinson Boyer, Louisa; Feng, Wei; Gulbis, Natallia; Hajdu, Klara; Harrison, Richard J.; Jeffries, Peter; Xu, Xiangming (Frontiers in Plant Science, 2016)
Strawberry is an important fruit crop within the UK. To reduce the impact of soil-borne diseases and extend the production season, more than half of the UK strawberry production is now in substrate (predominantly coir) under protection. Substrates such as coir are usually depleted of microbes including arbuscular mycorrhizal fungi (AMF) and consequently the introduction of beneficial microbes is likely to benefit commercial cropping systems. Inoculating strawberry plants in substrate other than coir has been shown to increase plants tolerance to soil-borne pathogens and water stress. We carried out studies to investigate whether AMF could improve strawberry production in coir under low nitrogen input and regulated deficit irrigation. Application of AMF led to an appreciable increase in the size and number of class I fruit, especially under either deficient irrigation or low nitrogen input condition. However, root length colonisation by AMF was reduced in strawberry grown in coir compared to soil and Terragreen. Furthermore, the appearance of AMF colonising strawberry and maize roots grown in coir showed some physical differences from the structure in colonised roots in soil and Terragreen: the colonization structure appeared to be more compact and smaller in coir.